Genetic evidence that uptake of the fluorescent analog 2NBDG occurs independently of known glucose transporters - D’Souza, Lucas J.; Wright, Stephen H.; Bhattacharya, Deepta (PLOS ONE, 2022)
The fluorescent derivative of glucose, 2-Deoxy-2-[(7-nitro-2,1,3-benzoxadiazol-4-yl)-amino]-D-glucose (2NBDG), is a widely used surrogate reagent to visualize glucose uptake in live cells at single cell resolution. Using CRISPR-Cas9 gene editing in 5TGM1 myeloma cells, we demonstrate that ablation of the glucose transporter gene Slc2a1 abrogates radioactive glucose uptake but has no effect on the magnitude or kinetics of 2NBDG import. Extracellular 2NBDG, but not NBD-fructose was transported by primary plasma cells into the cytoplasm suggesting a specific mechanism that is unlinked from glucose import and that of chemically similar compounds. Neither excess glucose nor pharmacological inhibition of GLUT1 impacted 2NBDG uptake in myeloma cells or primary splenocytes. Genetic ablation of other expressed hexose transporters individually or in combination with one another also had no impact on 2NBDG uptake. Ablation of the genes in the Slc29 and Slc35 families of nucleoside and nucleoside sugar transporters also failed to impact 2NBDG import. Thus, cellular uptake of 2NBDG is not necessarily a faithful indicator of glucose transport and is promoted by an unknown mechanism.